Optimization of the Supply Chain of Aromatic and Medicinal Plants (AMP): Challenges and Strategies - KAOUTAR CHBANI; JAOUAD BOUARFA (International Journal of Scientific Research and Innovative Studies, 2024)
ABSTRACT This article describes the main challenges that affect the flow of the aromatic and medicinal plants (AMP) chain. Some of the area highlighted in the article include supplier management, production, processing, customization, meeting the standard and the regulation, acquiring and procuring, transportation, and marketing. It also identifies the main challenges facing this chain and proposes several avenues to improve the competitiveness and sustainability of the AMP industry: concentrate scientific information, utilize such tools as management of growth cycles with the help of modern technologies, and develop various supplies as well as transport facilities. The ultimate strategy is to enhance the concepts of sustainable growth and improve the opportunities for economic and social gain. Keywords: Aromatic and Medicinal Plants (PAM), Supply Chain, Supplier Selection, Production and Processing, Marketing. Received Date: April 15, 2024 Accepted Date: May 13, 2024 Published Date: June 01, 2024 Available Online at: https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/162 DOI: https://doi.org/10.5281/zenodo.12544194